Thermal-hydraulic performance of solar receiver duct with inclined punched-ribs and grooves - Jayranaiwachira, Nuthvipa; Promvonge, Pongjet; Thianpong, Chinaruk; Skullong, Sompol (My University, 2022)
The article presents an experimental study on turbulent airflow friction and thermal behaviors in a solar receiver heat exchanger duct mounted with combined inclined chamfered-groove and turbulators. The experimental work was conducted for Reynolds numbers from 5,300 to 24,000, based on the hydraulic duct diameter. The 45°-inclined punched-ribs and grooves were placed periodically on the absorber plate. The punched-rib parameters were four inclination angles (β = 0°, 45°, 90° and 135°) of the punched holes and three relative rib pitches (PR = 1, 1.5 and 2) whereas only a rib blockage ratio (BR = 0.5) and an angle of attack (α) of 45° were fixed. Similarly, the parameters of the grooves included only three groove-pitch ratios (PR), similar to the rib pitches and one groove blockage ratio (BR = 0.2). The experimental result has revealed that the combination of rib-groove turbulators at β = 0° (solid rib) and PR = 1 gives the maximum heat transfer rate and friction loss while the greatest thermal enhancement factor of 2.1 was found at β = 45°, PR = 1. Moreover, the friction loss and heat transfer correlations for this thermal system were determined.
Keywords: Heat transfer; Inclined rib; Solar receiver; Thermal performance; Turbulators